Biogas production from distillery slops using a multi-stage filter reactor - Demafelis, Rex B. (1990)
The performance characteristics of a newly designed Multi Stage Filter Reactor was investigated on the bases of gas productivity, COD removal, methane content and process stability. Distillery slops, a high strength industrial waste was used as a substrate in the anaerobic digestion. An average gas productivity of 25 liter gas per liter feed at slops COD content of 73,920 mg/liter. Average methane content and COD removal were 68.8% and 75.97%, respectively.
The pH of the effluent was stable at 7.3 to 7.8. Alkalinity range was high at 7,090 to 7,980 mg COD/l. highest organic loading was at 1,304 mg COD/liter day. The overall performance was determined in terms of methane yield per gram COD removed. Percent methane yield based on theoretical maximum is 79.2%.
Typescript.
Thesis (M.S.)--University of the Philippines Diliman.
Keywords: Biogas